Hepatoprotective Effect of Baicalein Against Acetaminophen-Induced Acute Liver Injury in Mice - Zhou, Hong-Chao; Wang, Hui; Shi, Kun; Li, Jian-Ming; Zong, Ying; Du, Rui (Molecules (Basel, Switzerland), 2018)
Baicalein (BAI), one of the main components of Scutellaria baicalensis Georgi, possesses numerous pharmacological properties, including anti-cancer, anti-oxidative, anti-virus and anti-bacterial activities. The purpose of this study was to evaluate the hepatoprotective effect of baicalein against acetaminophen (APAP)-exposed liver injury in mice, and elucidate the underlying hepatoprotective mechanism. Baicalein pretreatment significantly alleviated the elevation of IL-6, IL-1β and TNF-α in serum and hepatic in a dose-dependent manner. It also dose-dependently reduced the hepatic malondialdehyde (MDA) concentration, as well as the depletion of hepatic superoxide dismutase (SOD), hepatic glutathione (GSH) and hepatic catalase (CAT). Moreover, pretreatment with baicalein significantly ameliorated APAP-exposed liver damage and histological hepatocyte changes. Baicalein also relieved APAP-induced autophagy by regulating AKT/mTOR pathway, LC3B and P62 expression. Furthermore, the hepatoprotective effect of baicalein to APAP-induced liver injury involved in Jak2/Stat3 and MAPK signaling pathway. Taken together, our findings suggested that baicalein exhibits the ability to prevent liver from APAP-induced liver injury and provided an underlying molecular basis for potential applications of baicalein to cure liver injuries.